Rekonstruksi Kebijakan Vaksinasi Warga Binaan Permasyarakatan Di Masa Pandemi: Keadilan Hukum Dan Hak Asasi Manusia Bagi Masyarakat Rentan - Christian Todo; Desak Putu Risma Widyantari (Lex Renaissance, 2021)
This study aims to analyze: first, the causes of the non-optimal implementation of vaccination for inmates (Warga Binaan Pemasyarakatan, WBP) during the pandemic. Second, the ratio of the importance of optimizing vaccination for WBP in Correctional Institutions (Lapas) during the pandemic. Third, the solution in optimizing vaccination for inmates during the pandemic. This study uses a normative legal research method with a statutory and conceptual approach. The results of this study conclude that first, that vaccination is not optimal for inmates due to: a) from the aspect of legal substance, the absence of a definition of vulnerable groups and the absence of regulations that regulate the flow of coordination and technical procedures for vaccination in prisons; b) from the aspect of legal structure, criminal penalties in prisons are still dominantly applied, which causes overcrowded problems; c) from the aspect of legal culture, the WBP's conservative paradigm is habitually. Second, regarding the significance of vaccination for inmates, it is actually the absolute responsibility of the state to respect, protect, and fulfill the implementation of the rights of inmates. Optimization of WBP vaccination is needed to create herd immunity holistically. Third, optimizing vaccination for inmates using preventive mechanisms that are oriented towards minimizing the inflow of prisoners to prisons as well as repressive mechanisms, revising or forming regulations that clarify the provisions of 'Vulnerable Communities' according to the Strategic Advisory Group of Experts on Immunization, removing the administrative requirements for National Identification Numbers and implement special outreach programs.Keywords: Covid-19; inmates; pandemic; vaccination; vulnerable societyAbstrakPenelitian ini bertujuan ingin menganalisis: pertama, penyebab ketidakoptimalan implementasi vaksinasi bagi Warga Binaan Pemasyarakatan (WBP) pada masa pandemi. Kedua, ratio pentingnya optimalisasi vaksinasi bagi WBP di Lembaga Permasayarakatan (Lapas) pada masa pandemi. Ketiga, solusi dalam mengoptimalkan vaksinasi bagi WBP pada masa pandemi. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian ini menyimpulkan, pertama, ketidakoptimalan vaksinasi bagi WBP disebabkan atas: a) dari aspek legal legal substance, tidak adanya definisi kelompok rentan serta ketiadaan regulasi yang mengatur alur koordinasi dan prosedur teknis vaksinasi di Lapas; b) dari aspek legal structure, penjatuhan pidana di Lapas masih dominan diterapkan, yang menyebabkan persoalan overcrowded; c) dari aspek legal culture, menghabituasinya paradigma konservatif WBP. Kedua, mengenai signifikansi vaksinasi bagi WBP, sejatinya menjadi tanggung jawab absolut dari negara untuk menghormati, melindungi, dan memenuhi penyelenggaraan hak WBP. Optomalisasi vaksinasi WBP diperlukan untuk menciptakan herd immunity secara holistik. Ketiga, optimalisasi vaksinasi bagi WBP menggunakan mekanisme preventif yang berorientasi untuk meminimalisir arus masuk narapidana ke Lapas serta mekanisme represif, merevisi maupun membentuk regulasi yang memperjelas ketentuan ‘Masyarakat Rentan’ sesuai Strategic Advisory Group of Experts on Immunization, menghapus ketentuan syarat administratif Nomor Induk Kependudukan dan menerapkan program penjangkauan khusus.Kata Kunci:  Pandemi; covid-19; vaksinasi; masyarakat rentan; warga binaan pemasyarakatan